Successively Equatorward Propagating Ionospheric Acoustic Waves and Possible Mechanisms Following the Mw 7.5 Earthquake in Noto, Japan, on 1 January 2024 - Bing Zhang; Tong Liu; Xueshang Feng; Guochang Xu (Space Weather, 2025)
Abstract On 1 January 2024, the Mw 7.5 Noto Peninsula earthquake in Japan generated ionospheric disturbances detected via dense GNSS networks. Significant coseismic acoustic waves emerged ∼8 min post‐event, exhibiting 0.3 TECU amplitudes, 2–8 min periods, and ∼1 km/s propagation speeds. These disturbances propagated exclusively southward as arc‐shaped fronts. The observed anisotropy aligns closely with the local geomagnetic field orientation (declination 8.7°), suggesting magnetic channeling as a key factor. Secondary factors likely include northward thermospheric winds suppressing northward wave propagation and land‐ocean coupling efficiency differences, which enhanced vertical displacements over southern continental regions. Notably, weak disturbances linked to the Mw 6.2 aftershock were detected, challenging conventional magnitude thresholds for ionospheric detection. While the mainshock's CID dynamics reflect known magnetic guidance mechanisms, the southward preference highlights site‐specific interactions between seismic forcing and geophysical filters. This study provides new observational evidence of earthquake‐ionosphere coupling, emphasizing the detectability of moderate‐magnitude events under favorable conditions, with implications for space weather monitoring and multi‐scale seismic hazard assessment.